Fire-adapted traits of Pinus arose in the fiery Cretaceous - He, Tianhua; Pausas, J.; Belcher, C.; Schwilk, D.; Lamont, Byron (Wiley-Blackwell Publishing Ltd., 2012)
The mapping of functional traits onto chronograms is an emerging approach for the identification of how agents of natural selection have shaped the evolution of organisms. Recent research has reported fire-dependent traits appearing among flowering plants from 60 million yr ago (Ma). Although there are many records of fossil charcoal in the Cretaceous (65–145 Ma), evidence of fire-dependent traits evolving in that period is lacking. We link the evolutionary trajectories for five fire-adapted traits in Pinaceae with paleoatmospheric conditions over the last 250 million yr to determine the time at which fire originated as a selective force in trait evolution among seed plants. Fire-protective thick bark originated in Pinus c. 126 Ma in association with low-intensity surface fires. More intense crown fires emerged c. 89 Ma coincident with thicker bark and branch shedding, or serotiny with branch retention as an alternative strategy. These innovations appeared at the same time as the Earth’s paleoatmosphere experienced elevated oxygen levels that led to high burn probabilities during the mid-Cretaceous. The fiery environments of the Cretaceous strongly influenced trait evolution in Pinus. Our evidence for a strong correlation between the evolution of fire-response strategies and changes in fire regime 90–125 Ma greatly backdates the key role that fire has played in the evolution of seed plants.